Arsenic Removal from Drinking Water Using Low Pressure Membranes - Elcik, Harun; Cakmakci, Mehmet; Sahinkaya, Erkan; Ozkaya, Bestamin (AMER CHEMICAL SOC, 2013)
Arsenic removal from drinking water using low-pressure membranes together with chemical oxidation and adsorption on ferric iron coagulates was deeply investigated. Hypochlorite or ozone was used to oxidize arsenite (100 or 1000 mu g/L) and ferrous iron (0.5-20 mg/L) simultaneously. As(III) or As(V) rejection by ultrafiltration was negligible. Although partial As(III) rejection was possible in the presence of ferric iron, treated effluent did not meet the drinking water standards. Oxidation of As(III) and Fe(II) to As(V) and Fe(III), respectively, significantly increased arsenic rejection by low pressure membranes. Arsenic rejection performance depended on the type and concentration of oxidants used, concentration of Fe(II), and the type of membrane. In general, the hypochlorite + Fe(II) + membrane process gave much better performance compared with the ozone + Fe(II) + membrane process. All the membranes used in this study were effective to decrease arsenic concentration from 100 or 1000 mu g/L to the target value (10 mu g/L) in the presence of sufficient iron and oxidant concentrations. Hence, the flux values of different membranes should be considered for an economical point of view.
Keywords: CONTAMINATED WATER; IRON-OXIDE; OXIDATION; FILTRATION; ADSORPTION; NANOFILTRATION; NANOPARTICLES; COAGULATION; PH; Engineering